Enhancing interactions between cells and hierarchical micro/nanostructured TiO2 films for efficient capture of circulating tumor cells. (26th July 2021) - Wu, Xingda; Tang, Nan; Liu, Cuijuan; Zhao, Qin; Liu, Xingyan; Xu, Qiuyan; Chen, Chunmei; Sun, Binying; Chen, Hongpeng
Abstract: Micro/nano hierarchical substrates with different micropillar spacings were designed and prepared for capture of tumor cells. The cell capture efficiency of hierarchical substrates with low-density micropillar arrays was similar to that of nanostructured substrate. Increasing the density of micopillars could significantly improve the capture efficiency. The maximum capture efficiency was achieved on the hierarchical substrate with micropillar spacings of 15 μ m, but further reducing the micropillar spacings did not increase the cell capture efficiency. It was also found that hierarchical substrates with appropriate spacing of micropillars appeared more favorable for cell attachment and spreading, and thus enhancing the cell-material interaction. These results suggested that optimizing the micropillar arrays, such as the spacing between adjacent micropillars, could give full play to the synergistic effect of hierarchical hybrid micro/nanostructures in the interaction with cells. This study may provide promising guidance to design and optimize micro/nano hierarchical structures of biointerfaces for biomedical application.